2004
DOI: 10.1093/molbev/msh223
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution of Sex-Biased Genes in Drosophila

Abstract: Studies of morphology, interspecific hybridization, protein/DNA sequences, and levels of gene expression have suggested that sex-related characters (particularly those involved in male reproduction) evolve rapidly relative to non-sex-related characters. Here we report a general comparison of evolutionary rates of sex-biased genes using data from cDNA microarray experiments and comparative genomic studies of Drosophila. Comparisons of nonsynonymous/synonymous substitution rates (d(N)/d(S)) between species of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
188
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(214 citation statements)
references
References 81 publications
22
188
3
1
Order By: Relevance
“…Maleand female-biased genes, especially if sex-biased gene expression has arisen from sexual antagonism, are predicted to have nonrandom genomic distributions depending on the heterogametic system (Rice 1984) or incomplete dosage compensation. This could influence studies of fast-Z as male-biased genes evolve more quickly (Zhang et al 2004;Zhang and Parsch 2005), possibly because of their involvement with sexual selection or malemale competition. If these genes are over-or under-represented on the sex chromosome, this will impact on the mean rates of divergence of sex-linked genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maleand female-biased genes, especially if sex-biased gene expression has arisen from sexual antagonism, are predicted to have nonrandom genomic distributions depending on the heterogametic system (Rice 1984) or incomplete dosage compensation. This could influence studies of fast-Z as male-biased genes evolve more quickly (Zhang et al 2004;Zhang and Parsch 2005), possibly because of their involvement with sexual selection or malemale competition. If these genes are over-or under-represented on the sex chromosome, this will impact on the mean rates of divergence of sex-linked genes.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the avian Z chromosome has an excess of coding regions that exhibit a male-biased expression pattern (Kaiser and Ellegren 2006;Storchova and Divinia 2006), which has been shown to be positively correlated with the rate of evolution Zhang et al 2004;Zhang and Parsch 2005). Therefore, we wanted to investigate the relationship between gene expression pattern and d N /d S values in order to determine whether the pattern of fast-Z described above is simply the result of the hyperaccumulation of male-biased genes on the avian Z chromosome.…”
Section: Divergence Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Within these sex-biased genes, those with male-biased expression tend to show greater difference in expression levels than do female-biased genes or non-sex-biased genes in both within-and between-species comparisons Parisi et al 2003Parisi et al , 2004Ranz et al 2003). In addition, rates of sequence evolution of sex and reproduction-related (SRR) and non-SRR genes differ quite dramatically: male and female SRR genes evolve faster than non-SRR genes (Begun et al 2000;Swanson et al 2001;Zhang et al 2004;Jagadeeshan and Singh 2005;Mueller et al 2005;Proschel et al 2006;Lawniczak and Begun 2007; see Swanson and Vacquier 2002 for review).…”
mentioning
confidence: 99%
“…Such studies reported that genes expressed in the testis and genes encoding seminal fluid proteins include many that evolve rapidly (Begun et al 2000Swanson et al 2001;Holloway and Begun 2004;Kern et al 2004;Zhang et al 2004;Begun and Lindfors 2005;Mueller et al 2005;Wagstaff and Begun 2005a;Schully and Hellberg 2006). Many female reproductive proteins have also been shown to evolve faster than non-sexspecific proteins (Civetta and Singh 1995;Jansa et al 2003;Swanson et al 2004;Jagadeeshan and Singh 2005).…”
mentioning
confidence: 99%